50 years of Lithuanian Mathematical Society conferences - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2008)
A survey of the activities of the Lithuanian Mathematical Society is given.
Keywords: Lithuanian Mathematical Society; conferences